Hyperscanning fNIRS data analysis using multiregression dynamic models: an illustration in a violin duo - do Nascimento, Diego Carvalho; Santos da Silva, José Roberto; Ara, Anderson; Sato, João Ricardo; Costa, Lilia (Frontiers in Computational Neuroscience, 2023)
Interpersonal Neural Synchronization (INS) demands a greater understanding of the influence that a brain may carry on others. Therefore, brain synchronization is an even more complex system to be investigated than intrasubject brain connectivity. The development of novel methods for statistical inference in this context is necessary. In this paper, we propose the two-step network estimation: Tabu search local method, then, global maximization in the selected subgroup (partial conditional directed acyclic graph (DAG) + Multiregression Dynamic Model) motivated by the analysis of fNIRS hyperscanning data. We illustrate this approach in a dataset of two individuals who are playing the violin together. This study contributes to new tools for the Social Neuroscience field, which may provide new perspectives about intersubject interactions. Our proposed approach estimates the best probabilistic network representation, in addition to enabling the time-varying parameters, which may be helpful in understanding the brain-to-brain association of these two players. The illustration of the violin duo highlights time-evolving changes in the brain activation of an individual influencing the other one through data-driven analysis. We confirmed that one player was leading the other given the ROI causal relation towards this other player.